How Does Pension Eligibility Affect Labor Supply in Couples? - Rafael Lalive; Pierpaolo Parrotta (Institute for the Study of Labor (IZA), 2016)
Many OECD countries are reforming their pension systems. We investigate how pension eligibility affects labor supply in couples. Inspired by a theoretical framework, we measure how the sharp change in the pension eligibility of both partners affects labor force participation. We find that both partners leave the labor force as they become eligible for a pension. The effect of their own pension eligibility is 12 percentage points for women and 28 percentage points for men. Women also reduce their labor force participation by 2 to 3 percentage points as their partner reaches pension eligibility. For men, the effect of their partner's eligibility is smaller and not significantly different from zero. For women and men with low education, the effect of their own eligibility is strong. Regardless of education level, the partner eligibility effect is strong in homogamous couples. Studying joint labor supply, we find that pension eligibility reduces labor supply in couples by 44 percentage points, approximately 4 percentage points more than in a model that ignores partner eligibility effects.
Keywords: J26; J14; C40; D10; 330; household decisions; full retirement age; pension eligibility; couple labor supply